Exploration, Creation And Evaluation Of Plant Image In Ceramic Artworks In Jingdezhen City, China - Sun, Xiaoli (2024)
Contemporary PICA combines ceramic media with a long history, plant motifs, and modern innovative thinking. Significant changes have taken place compared with the past. However, regarding theory, the research on plant motif, cultural meaning, creation technique, and application form is insufficient in China. Regarding practice, the plant motif is outdated, and ceramic artists must try to implement innovation and update the traditional creation mode. Therefore, this research aims to explore the application, creation, and innovation of plant images in contemporary ceramic artworks. First, discovers the aesthetic characteristics, cultural meanings, application forms and expressive features of plant image in ceramic artworks through literature research and observation. Second, uses questionnaire survey and expert interview method to research and collect data. The SPSS software was used to quantitatively analysis the data of 103 respondents, aiming to understand people's perception and preference for PICA and variant correlation and influence relationships. NVivo’s software conducted a qualitative analysis of the interview content of 6 ceramic experts and explored the main concerns and thinking angles of creation. Third, apply experimental creation method to implement the practice, collecting various plant images for modelling and texture, collage and hollowing, colour experiment, and comprehensive material creation. The results show that: (1) 46.6% respondents prefer flower motifs, culture meaning showing personal expectations, natural materials, abstract and creative shapes, rich glaze or texture, handmade, and used in home decoration.